Analisis dan Perbaikan Usability Situs Computer Assisted Test Sistem Informasi menggunakan Metode Design Thinking dan System Usability Scale - Muhammad Hilmy Musyafa; Retno Indah Rokhmawati; Kariyoto Kariyoto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
The Computer Assisted Test Information System site or commonly abbreviated as CAT-SI is one of the sites owned by the Faculty of Computer Science, Universitas Brawijaya. The CAT-SI website has a purpose, namely to meet the needs of online student learning evaluations, especially during the end of semester exams due to adjusting to the conditions of the Covid-19 pandemic. The CAT-SI site development process tends to be short because the needs are quite urgent, so further development and improvement of the display, information structure, and several features such as live meetings, chat, notifications, and exam calendars are needed. The Design Thinking method can be a solution to produce a website design that suits the needs of users in this study, because no research has been conducted on the CAT-SI site before so it is necessary to increase the needs of users more deeply by taking an empathetic approach. In its application, the Design Thinking method has 5 process stages, namely empathize to explore user needs, determine to analyze and determine problems, ideas to make points and design solutions, prototypes to make products that can be tested, and test the level of validation to users. The initial and final evaluation stages of the study used the System Usability Scale (SUS) questionnaire. The comparison result of the average value obtained during the evaluation is 43.5 to 77 points. which the points meet the categories of â€œAcceptableâ€, â€œGoodâ€, on â€œBâ€.